Abundance does not predict extinction risk in the fossil record of marine plankton - Sarah Trubovitz; Johan Renaudie; David Lazarus; Paula J. Noble (Communications Biology, 2023)
Abstract A major premise of ecological neutral theory is that population size is inversely related to extinction risk. This idea is central to modern biodiversity conservation efforts, which often rely on abundance metrics to partially determine species extinction risk. However, limited empirical studies have tested whether extinction is indeed more probable for species with low abundances. Here we use the fossil record of Neogene radiolaria to test the relationship between relative abundance and longevity (time from first to last occurrence). Our dataset includes abundance histories for 189 polycystine radiolarian species from the Southern Ocean, and 101 species from the tropical Pacific. Using linear regression analyses, we show that neither maximum nor average relative abundance are significant predictors of longevity in either oceanographic region. This suggests that neutral theory fails to explain the plankton ecological-evolutionary dynamics we observe. Extrinsic factors are likely more important than neutral dynamics in controlling radiolarian extinction.